ASIC1a involves the acid-mediated activation of pancreatic stellate cells associated with autophagy induction - Wang, Tao; Wang, Qianqian; Pan, Guixia; Jia, Guorong; Li, Xiao; Wang, Chao; Zhang, Liming; Zuo, Changjing (Physiological research, 2023)
The acidic tumor microenvironment (TME) of pancreatic cancer affects the physiological function of pancreatic stellate cells (PSCs), which in turn promotes cancer progression. Acid-sensing ion channel 1a (ASIC1a) is responsible for acidosis-related physiopathological processes. In this study, we investigated the effect of acid exposure on the activation and autophagy of PSCs, and the role of ASIC1a in these events. The results showed that acidic medium upregulated the expression of ASIC1a, induced PSCs activation and autophagy, which can be suppressed by inhibiting ASIC1a using PcTx1 or ASIC1a knockdown, suggesting that ASIC1a involves these two processes. In addition, the acid-induced activation of PSCs was impaired after the application of autophagy inhibitor alone or in combination with ASIC1a siRNA, meaning a connection between autophagy and activation. Collectively, our study provides evidence for the involvement of ASIC1a in the acid-caused PSCs activation, which may be associated with autophagy induction.
Keywords: Acid Sensing Ion Channels; Pancreatic Stellate Cells; krysa rodu Rattus; pankreatické hvězdicovité buňky; autofagie; iontové kanály ASIC; Animals; Autophagy; potkani Sprague-Dawley; zvířata; Rats, Sprague-Dawley; Rats